Políticas e práticas no planejamento escolar em Minas Gerais no final do século XX - Valente, Lucia de Fatima (2002)
This research is in the field of study of the planning area and politics in education, taking as focus the experience developed in the State of Minas in the end of the 90’s of the century XX. We tried to understand the elaboration process of the Plan of Development of the School (PDE), with the objective of analyzing the contours assumed by the autonomy’s principies, of the participation and of the democratization of the school management, as well as the own planning conception extolled in the official guidelines and its unfoldings in educational school practice. So, besides a careful bibliographical revision around the thematic, we proceeded equally to the analysis of the official guidelines emanated by the State Clerkship of Education of Minas Gerais (SEE/MG), that sought to guide the planning of the school work in the public schools of Minas Gerais, as well as the opinions emitted by the State Council of Education of Minas Gerais (CEE/MG) in the same period and, that talks about the investigated theme. We accomplished, also, a empiric research with the professionals of the public education system, directors, teachers and educational supervisors involved in the process of construction of PDE in the respective schools. We analyzed the different theoretical conceptions of educational planning, from the traditional Normative Planning, to the contours of the Pedagogic Political Project. We still analyzed, the unfoldings of the neoliberal proposals in the society and in the Brazilian education, as well as its contours in the public education of Minas Gerais. For that, we demarcated the contours of that idea in the end of that same century, by the analysis of the international organisms guidelines, more specifically, of the World Bank and its impacts in the educational field in Brazil and Minas Gerais. At the same time in that we used the guidelines that guided the school planning organization of Minas Gerais in the 90’s, of last century, we presented data that make possible to understand how this process grew at the schools, starting from the subjects interviewees' reports. In other words, we tried to investigate in what measured and what forms the official guidelines of SEE/MG were assimilated in the construction practices of PDE, for the subjects whom built such practices. At the end, our conclusions are presented and show that when recovering the traveled path, we try to answer the questions made, as well as to point new inquietudes, new challenges. The results of this study reveal that, in the scope of the educational politics in Minas Gerais, those conceptions of planning with normative character prevail, prescriptive, present in the Strategic Planning and in the model of Total Quality Management. We evidenced, also, the functional and operative character of participation that those approaches carry. We discussed the terminological and conceptual variation, present in the official guidelines around the subject of the school planning and its implications in the daily practices of public system educational units, mainly in what refers to the desarticulation among planning, autonomy construction, participation and democratization of the school management.